"Another Tool in Your Toolkit": Pediatric Occupational and Physical Therapists' Perspectives of Initiating Telehealth during the COVID-19 Pandemic. (3rd September 2022) - Wittmeier, Kristy D. M.; Hammond, Elizabeth; Tymko, Kaitlyn; Burnham, Kristen; Janssen, Tamara; Pablo, Arnette J.; Russell, Kelly; Pierce, Shayna; Costello, Carrie; Protudjer, Jennifer L. P.
Abstract: Aims: Pediatric occupational and physical therapy service delivery via telehealth increased during the COVID-19 pandemic. Real-world experience can guide service improvement. This study explored experiences, barriers, and facilitators of initial telehealth implementation from the therapist's perspective. Methods: Qualitative descriptive approach. Semi-structured interviews were conducted with occupational therapists (n = 4) and physical therapists (n = 4) between May-June 2020. Interviews were recorded, and transcribed verbatim. Data were coded inductively to generate themes, then re-coded deductively to classify barriers and facilitators to telehealth acceptance and use using the Unified Technology Acceptance Theory. Results: Participants had 16.5 [(2-35); median (range)] years of experience (3 months with telehealth) and predominantly worked with preschool children. Three themes about telehealth were identified: a practical option; requires skill development and refinement; beneficial in perpetuity. Most frequently cited barriers were the lack of opportunity for 'hands-on' assessment/intervention and the learning curve required. Most frequently cited facilitators included seeing a child in their own environment, attendance may be easier for some families, and families' perception that telehealth was useful. Conclusion: Despite rapid implementation, therapists largely described telehealth as a positive experience. Telehealth facilitated continued service provision and was perceived as relevant post-pandemic. Additional training and ensuring equitable access to services are priorities as telehealth delivery evolves.